BENTENG PERTAHANAN IDEOLOGI KERENTANAN REMAJA TERHADAP SIBER-RADIKALISASI DAN TRANSFORMASI KETAHANAN MULTITINGKAT DI INDONESIA - Yosua Cahyo Pratomo; Sri Murtiana (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the patterns of youth exploitation in the cyber-radicalization phenomenon in Indonesia and formulate a Multi-Level Resilience Transformation framework as an adaptive ideological bulwark against contemporary threats. Using narrative literature and qualitative policy analysis methods, this study examines literature and regulations post-2024 institutional restructuring to build an integrated defense model. The results show that adolescent psychosocial vulnerability (Identity vs. Role Confusion) is exploited through online grooming patterns, such as love bombing and the use of global issues as triggers, which leads to divided loyalties and the risk of prolonged trauma. The novelty of this study lies in the integration of three dimensions simultaneously: developmental psychology, community resilience, and national policy architecture within a multi-level framework specific to the Indonesian context. The framework consists of: (1) Self-Resilience through critical digital literacy and empathetic resilience; (2) Community Resilience with the empowerment of women as early detection agents and optimization of online religious figures; and (3) National Resilience that synergizes the policies of the National Counterterrorism Agency (BNPT), Komdigi, the Ministry of Elementary and Secondary Education, and the Ministry of Education and Science and Technology. The practical implications include the availability of an implementation roadmap for relevant ministries, while the academic contribution enriches the literature on digital resilience and youth vulnerability in Southeast Asia, while also offering a trauma-informed approach to re-entry programs for victims of radicalization.